Implementation of Odoo Erp At Petrodollar Coffeeatery & Roastery - Aritonang, Bagus Aditya; Is Mardianto; Teddy Siswanto (Intelmatics, 2025)
In carrying out business processes in Petro Dollar Coffeeatery & Roastery, of course, there are various problems such as in the recording, data collection, and warehousing sections related to efficiency matters. Currently, most of the process is still done manually using just conventional recording on paper, which results in work requiring more time and manpower. In addition, data and information owned by a department cannot automatically be accessed by other departments that are actually related to their business processes and need the data. By implementing ERP software such as Odoo 12.0, you can overcome existing problems because recording and data collection is done automatically and decisions can be made quickly and accurately. By implementing this system, it is expected to increase efficiency and effectiveness of performance and minimize errors in work.